2017
DOI: 10.1002/anie.201708119
|View full text |Cite
|
Sign up to set email alerts
|

Elucidating the Excited State of Mechanoluminescence in Organic Luminogens with Room‐Temperature Phosphorescence

Abstract: Two stable, purely organic luminogens exhibit both mechano- (ML) and photoluminescence (PL) with dual fluorescence-phosphorescence emissions at room temperature. Careful analysis of the crystal structures, coupled with theoretical calculations, demonstrate that room-temperature phosphorescence and ML properties are strongly related to molecular packing. In particular, the formation and fracture of molecular dimers with intermolecular charge-transfer properties has a significant effect on intersystem crossing, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
139
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 235 publications
(142 citation statements)
references
References 32 publications
1
139
0
2
Order By: Relevance
“…In particular,t he transformations of molecular conformation, such as trans-cis isomerization and excitedstate intramolecular proton transfer (ESIPT), have often been used to realize the dynamic PL process. [8] Then the questions arise whether the ML process is also sensitive to the molecular conformation or whether is it just the same as the PL behavior. [7] Inspired by similar energy level features between ML and PL processes,w et hen made an initial attempt to reveal the excited state of mechanoluminescence in the organic luminogen CzS-C 2 H 5 with the mature PL theory acting as template in 2017, and found that the change of packing mode under the mechanical stimulus played an important role in the ML process.…”
mentioning
confidence: 99%
“…In particular,t he transformations of molecular conformation, such as trans-cis isomerization and excitedstate intramolecular proton transfer (ESIPT), have often been used to realize the dynamic PL process. [8] Then the questions arise whether the ML process is also sensitive to the molecular conformation or whether is it just the same as the PL behavior. [7] Inspired by similar energy level features between ML and PL processes,w et hen made an initial attempt to reveal the excited state of mechanoluminescence in the organic luminogen CzS-C 2 H 5 with the mature PL theory acting as template in 2017, and found that the change of packing mode under the mechanical stimulus played an important role in the ML process.…”
mentioning
confidence: 99%
“…[35] Phenothiazines are well-known classes of compounds for application in thermally activated delayed fluorescence (TADF), because of the ease of intersystem crossing from their singlet to triplet states and vice versa. [35] Phenothiazines are well-known classes of compounds for application in thermally activated delayed fluorescence (TADF), because of the ease of intersystem crossing from their singlet to triplet states and vice versa.…”
Section: Phosphorescent Triboluminescent Materialsmentioning
confidence: 99%
“…[5,13] Forisolated BrFluÀCBr, although there are two main channels with two minor channels,t he smallest energy gap of 0.1052 eV can be only found in aminor channel between S 1 and T 5 (Figure 4). Thec onfigurations of the excited state and possible ISC of monomers and dimers were calculated by the timedependent density-functional theory (TD-DFT).…”
mentioning
confidence: 99%
“…Actually,t he light is green-white and the difference is apparent under soft light (Figure 2e). [13] Furthermore,after continuous grinding, the crystalline sample was converted into powder with weak blue emission under the mechanical stimulus (Figure 2d, inset). [13] Furthermore,after continuous grinding, the crystalline sample was converted into powder with weak blue emission under the mechanical stimulus (Figure 2d, inset).…”
mentioning
confidence: 99%